Decoding the stars : a modern astrology guide to discover your life's purpose - Scott, Allison (Astrologer) (Wellfleet Press, 2023)
"Decoding the Stars provides guidance for self-development and gives direction to those struggling with life's challenges by examining the details of your birth chart and, through guided rituals, giving fresh, new life to the practice of astrology"--